EVALUASI TATA KELOLA TEKNOLOGI INFORMASI PADA RUMAH SAKIT DR. H. IBNU SUTOWO BATURAJA BERDASARKAN FRAMEWORK COBIT 5 - Sukmawati, Ade; Cholil, Widya; Rizal, Syahril (Gema Teknologi, 2020)
Control of information technology governance at this time is very influential for the organization in achieving its strategic objectives. Technology has become an important part in supporting a service, including in Dr.H. Ibnu Sutowo Baturaja. The hospital has SIMRS in supporting its services. So that governance should be well planned. This research was conducted to evaluate the management of information technology that supports the SIMRS. The results of this study are to find out the value of the level of maturity in Dr. H Ibnu Sutowo Baturaja. Evaluations were carried out using the standard COBIT 5 measurement framework. The focus of this study was the domain of Ensure Resource Optimization (EDM01), Manage the IT Management Framework (APO01) (APO07), Build, Acquire and Implement (BAI04) and Monitoring, Evaluation and Access (MEA01).